Effects of Mergers and Acquisitions on Firms Performance: Evidence from the US Biopharmaceutical Companies - Qiu, Zuolun (2015)
This study is based on 356 completed takeovers in pharma and biotech industries from 1996 to 2012, results of the overall sample suggest that acquirers in the US fail to realise significant announcement period returns. However, some sub-samples (grouped by their respective transaction-specific attributes) record significant shareholder’s returns, most of these groups report positive CARs, only acquisitions of public targets, stock financed transactions, and acquirers that have outperformed the market in the pre-acquisition period present negative CARs. Further, the acquirer’s magnitude of three-day CARs and three-year average sales growth after takeovers are employed to measure its post-acquisition performance. The capital market is more likely to response positively when acquirers presented strong sales power in the past or bought privately held companies, while negative stock market reactions may occur when bidders have outperformed the market in the pre-acquisition period; when focusing on the past performance of acquiring firms (one year prior to the announcement date), firms with relative high R&D intensity, financial strength and Tobin’s q prior to takeovers appear to achieve constant sales growth in the post-acquisition period, whereas increases in firm size are likely to get abnormal returns down.